The Impact of Human Activities on Corals - Yang, Yucheng (Transactions on Environment, Energy and Earth Sciences, 2024)
Coral reef ecosystems are one of the most vital and dynamic ecosystems on earth, teeming with a diverse array of marine life and playing a crucial role in maintaining the health of the oceans. By delving into the multifaceted impacts of human activities on coral reef ecosystems, this paper examines the devastating consequences of various anthropogenic factors, such as the booming tourism industry, the pervasive microplastic pollution problem, and oil spills and other forms of marine pollution. The protection and restoration of coral reef ecosystems through a wide range of measures provides a safer and healthier habitat for coral reefs, thereby ensuring that coral reefs can continue to play an important role in the marine ecosystem. Only by adopting such a comprehensive and proactive approach can humankind ensure the sustainable use of coral reefs. Furthermore, this article proposes a series of protective measures and strategic improvement plans designed to rehabilitate and restore coral reef ecosystems to their former glory, ensuring their survival for future generations to marvel at and benefit from.